Reducing Organic Load From Industrial Residual Process Brine With a Novel Halophilic Mixed Culture: Scale-Up and Long-Term Piloting of an Integrated Bioprocess - Mainka, Thomas; Herwig, Christoph; Pflügl, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract